2019
DOI: 10.1002/pchj.327
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of trust on the relationship between doctor–patient communication and patients' risk perception during treatment

Abstract: Doctor-patient communication interacts with patients' satisfaction to influence patients' risk perception. Current theories to explain this relationship have assumed particular psychological processes to explain observations of risk-sensitive behavior in an economic setting, but as of yet, they have not addressed whether it is adaptive for a decision-maker in a health-care situation. In addition, little is known about the role of interpersonal trust between doctor and patient. We surveyed 602 patients to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 49 publications
1
29
1
1
Order By: Relevance
“…8 La comunicación en el abordaje de la salud sexual El proceso de comunicación juega un papel importante en la mejora de la relación profesional-paciente y, en consecuencia, en el cumplimiento de las recomendaciones y el tratamiento. 9 Los profesionales de la salud pueden no estar preparados y sentirse incómodos a la hora de abordar a los pacientes con respecto a aspectos relacionados con la enfermedad y la sexualidad. 10 La oferta de una adecuada capacitación podría minimizar esta restricción y contribuir a cualificar el desempeño de estos profesionales, con el objetivo de familiarizarlos con los diferentes conceptos de género, orientación e identidad sexual.…”
unclassified
“…8 La comunicación en el abordaje de la salud sexual El proceso de comunicación juega un papel importante en la mejora de la relación profesional-paciente y, en consecuencia, en el cumplimiento de las recomendaciones y el tratamiento. 9 Los profesionales de la salud pueden no estar preparados y sentirse incómodos a la hora de abordar a los pacientes con respecto a aspectos relacionados con la enfermedad y la sexualidad. 10 La oferta de una adecuada capacitación podría minimizar esta restricción y contribuir a cualificar el desempeño de estos profesionales, con el objetivo de familiarizarlos con los diferentes conceptos de género, orientación e identidad sexual.…”
unclassified
“…Patients may feel more satisfied with their medical experience when they have received care conforming to their specific needs and values. 34 Others have shown that patients are likely to trust HCWs when they feel respected and perceive medical staff as attentive and honest, 7 which is helpful to relieve the patients' anxiety due to bad treatment outcomes. Although there is uncertainty and high risk in medical treatment, patients believe they will have a good clinical outcome once admitted to the hospital, regardless of the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing incidence of aggressive behavior by patients against health care workers (HCWs) in many countries, 1,2 especially in China, [3][4][5] which is considered to be an occupational hazard. 3 It is not considered an accidental event but to be caused by a combination of various factors, such as failed doctor-patient relationships (DPR), 6 a low-level of risk perception, 7 flawed medical systems, patients' increasing mistrust of hospitals and physicians, 8 dissatisfaction with staff attitude, 2 and media orientation. 9 Several researches have pointed out there is a direct relationship between the violence and the patients' medical experience.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, patients should recognize the limitations of medicine and understand that disease is the common enemy of doctors and patients. They should trust doctors fully and actively discuss treatment decisions with doctors to jointly ght against disease [27] . Doctors should fully explain the treatment plan and communicate with patients to reduce their misunderstanding of reasonable medical behavior.…”
Section: In Uence Of Patient and Implicationsmentioning
confidence: 99%